Ultra-Processed Food Consumption Patterns as an Early Risk Factor for Obesity and Cardiovascular Disease in Today's Adolescents: A Literature Review - Krishna Artanto (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2026)
Modern dietary shifts have increased ultra-processed food (UPF) consumption, particularly among adolescents, raising concerns about obesity and cardiovascular disease (CVD) risk. This review analyzes the relationship between UPF intake and obesity and CVD risk in adolescents based on evidence from observational and cohort studies conducted in Korea, Brazil, Canada, and Indonesia. Key parameters included UPF contribution to total energy intake, body mass index (BMI), waist circumference, and blood pressure. The analysis found that UPF accounts for up to 40% of daily energy intake in adolescents. High UPF consumption significantly increased the risk of central adiposity (OR: 1.9) and high cardiovascular risk (OR: 3.77). Consistent associations were observed across countries for increased risk of obesity, hypertension, and diabetes. In Indonesia, over 80% of adolescents regularly consume UPF, with 29% experiencing overnutrition. In conclusion, high UPF consumption is strongly associated with increased obesity and cardiovascular risk from adolescence. Targeted nutritional interventions and public health policies to restrict UPF intake are urgently needed to mitigate long-term health impacts.